Less than one‐third of hip fracture patients return to their prefracture level of instrumental activities of daily living in a prospective cohort study of 480 patients. Issue 8 (13th July 2018) - Moerman, Sophie; Mathijssen, Nina MC; Tuinebreijer, Wim E; Nelissen, Rob GHH; Vochteloo, Anne JH
Abstract : Aim: A significant loss of instrumental activities of daily living (IADL) after a hip fracture has been reported. The aim of the present study was to identify specific predictors for low IADL after a hip fracture, in order to target better postoperative care for these patients. Methods: A prospective observational cohort study of 480 hip fracture patients was carried out. IADL was measured at baseline, and after 3 and 12 months using the Groningen Activity Restriction Scale. Multivariable logistic regression analysis was carried out using age, sex, American Society of Anesthesiologists classification, prefracture living with a partner, prefracture living situation, prefracture use of walking aids, type of fracture, type of anesthesia, length of hospital stay, postoperative complications and prefracture IADL as potential predictors for low IADL after a hip fracture. The correlation between IADL, mobility and living situation, both at admission, and 3 and 12 months postoperatively, were measured. Results: Three months after hip fracture treatment, 24% of patients returned to their baseline IADL level, at 12 months postoperative this was 29%. Factors associated with a larger loss in IADL after a hip fracture were older age, prefracture living with a partner, prefracture living at home, prefracture use of walking aids and longer length of hospital stay. The correlation between IADL and living situation was 0.69, and between IADL and use of walking aids was 0.80. Conclusions: A return to prefracture IADL level was low. Healthier patients have a steeper decline in postoperative IADL.Geriatr Gerontol Int 2018; 18: 1244–1248 .